Cognição, mobilidade e qualidade de vida de idosos com amputação de membro inferior devido à úlcera de pé diabético: uma série de casos - Jéssica Lohane Brandão (2022)
INTRODUCTION: Amputation is defined as the complete or partial removal of a limb or body parts by surgical or traumatic means. It can be classified as a major or minor amputation. Major lower limb amputations are generally those performed above ankle level. OBJECTIVE: This study aims to explore the possible relationship between amputation, cognition, mobility, and quality of life in patients undergoing major amputation due to diabetic foot. METHODOLOGY: An exploratory number of cases was carried out in the Vascular Surgery ward of Hospital Risoleta Tolentino Neves, Belo Horizonte, Minas Gerais. To this end, elderly aged 60 years or older with Diabetes Mellitus (DM) who underwent major unilateral amputation due to PD complications were followed up during the hospitalization period and for 12 weeks after hospital discharge. They performed face-to-face evaluation within one week after amputation, and remotely after hospital discharge in weeks 3, 6, 9, and 12; applying cognitive and functional assessment protocols. Functional mobility was assessed by the perception of the elderly before hospitalization and after amputation, using the classification proposed by Khan. The Perme Scale was used to measure the patient's mobility. The participants' cognitive function was assessed on admission using the Mini-Mental State Examination (MMSE), and finally, quality of life was assessed using the generic quality of life questionnaire (SF6D). RESULT: Of the five individuals who participated in the research, four completed the assessment by week 12. Likewise, it was found that after a major amputation, one participant had cognitive impairment, according to the MMSE, and two had low scores in mobility and greater assistance according to the Perme Scale during the hospitalization period. Regarding the quality of life, using the SF6D instrument, all participants had worse health status and low quality of life during the hospitalization period. After 12 weeks, P1 remained with cognitive impairment and with the worst perception of quality according to the SF6D, and died two days after the 12-week evaluation. CONCLUSION: The present study revealed that there was a relationship between amputation on cognition, mobility, and quality of life in patients undergoing major amputation due to diabetic foot. However, it is suggested that cohort studies be carried out, to broaden the generalization of the associations between amputation time and other evaluated outcomes.